(Dis)connection between Multiculturalism, Higher Education and Health: Experiences of International Students in Portugal during the Covid-19 Pandemic - Juliana Chatti Iorio; Katielle Silva (Education Sciences, 2024)
Multiculturalism may point to the idea of ‘cohesion in diversity’, but if differentiated institutional policies and practices do not accompany it, it may contribute to promoting or deepening inequalities between different groups/cultures. Given the increase in students’ international mobility, multicultural awareness in Higher Education Institutions (HEIs) must be considered. Based on this idea, this article aims to answer: (i) what were the main health problems (physical and mental) that international students (IS) in Portugal experienced during the COVID-19 pandemic; and (ii) how they perceived their health rights in Portugal. To this end, we used data from an online survey, which was made available to all IS enrolled in a Portuguese HEI between April and May 2020, and from 22 online interviews conducted between September 2020 and January 2021 with some of these students. The results showed that the pandemic impacted the mental health of IS; fear, anxiety and stress were some of the symptoms experienced. Portuguese public health services have been perceived as untrustworthy by IS, and some students’ experience reinforces the untrustworthiness. The research shows the (dis)connection between multiculturalism, health, and HEIs. While HEIs promote multiculturalism, they have failed to provide answers in the field of health that take into account the specificities of their different student groups.